Morphine sulfate abuse-deterrent formulations for the treatment of chronic pain. Issue 11 (2nd December 2018) - Fanelli, Andrea; Sorella, Maria Cristina; Ghisi, Daniela
ABSTRACT: Introduction : Abuse-deterrent formulations have been developed to reduce inappropriate opioid use. The aim of this paper is to review existing literature about currently available morphine abuse-deterrent formulations. Areas covered : The US FDA has currently attributed an 'abuse-deterrent formulation' label to two different morphine compounds: an agonist/antagonist combination, and a morphine formulation with physical barrier. The combination of morphine sulfate and naltrexone showed bioequivalence with extended release morphine. Naltrexone was found in low levels or non-detectable in most of the patients. If the capsules are tampered, the orally available naltrexone would be released, causing a decreased euphoria expected by the use of morphine. The application of physical and chemical barriers to the active compound aims at preventing manipulation of the opioid tablet. This abuse-deterrent formulation obtained with a physical barrier did not reduce drug liking compared to ER morphine. Expert commentary : Available data from literature suggest that both formulations may offer an alternative with lower abuse potential in the treatment of chronic pain. Nevertheless, current evidence suggests that only a little percentage of abusers may stop abusing drugs as result of reformulation. More post-marketing studies are advocated to evaluate the real impact of abuse-deterrent formulations.